EFFECT OF OPERATING CASH FLOW AND ACCOUNTING PROFIT ON STOCK RETURN: (Case Study of LQ-45 Company in Indonesia Stock Exchange) - Intan Juniarti; Bambang Satriawan (PENANOMICS: International Journal of Economics, 2023)
This research aims to examine: (1) The Influence of Operating Cash Flow to Stock Return in 2013-2016, (2) The influence of Accounting Profit to Stock Return in 2013-2016, (3) The Influence of Operating Cash Flow and Accounting Profit Together to Stock Return in 2013-2016. The data in this research is secondary data obtained from the company's annual financial statements in the Indonesian Stock Exchange (IDX). This type of research is the research of causality. This research was conducted by using sample of 24 LQ-45 companies listed in Indonesia Stock Exchange during the period 2016 to 2019. The data analysis techniques used are descriptive statistics, classical assumption test, simple linear regression analysis and analysis multiple linear regression. Based on hypothesis testing by using t test, it is concluded that Operating Cash Flow is not positive influence on Stock Return and Accounting Profit have positive effect on Stock Return. Based on F test it is concluded that Operating Cash Flow and Accounting Profit simultaneously have a positive effect on Stock Return